2015
DOI: 10.1177/230949901502300204
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Fixation Pitfalls of a Highly Unstable Intertrochanteric Fracture Variant

Abstract: Purpose. To describe a variant of intertrochanteric fracture not well-characterised in the existing classification systems. Methods. 10 women and 2 men aged 59 to 98 (median, 80) years with intertrochanteric fractures characterised by a low intertrochanteric fracture, a basicervical fracture fragment, and a thin or fractured lateral wall with greater trochanteric comminution were reviewed. Results. The 12 fractures were classified as A2.1 (n=1), A2.2 (n=7), A2.3 (n=1), and A3 (n=3) according to the AO/OTA clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Helin et al reported that intramedullary nailing provides poorer stabilization of unstable fractures compared to stable fractures (16). In some previous reports, relatively high complication rates were noted in patients with unstable intertrochanteric fractures (3,17). From the viewpoint of treatment methods, Chun et al introduced a unique reduction technique using a 4.2-mm Steinmann pin for unstable intertrochanteric fractures (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Helin et al reported that intramedullary nailing provides poorer stabilization of unstable fractures compared to stable fractures (16). In some previous reports, relatively high complication rates were noted in patients with unstable intertrochanteric fractures (3,17). From the viewpoint of treatment methods, Chun et al introduced a unique reduction technique using a 4.2-mm Steinmann pin for unstable intertrochanteric fractures (18).…”
Section: Discussionmentioning
confidence: 99%
“…Osteosynthesis has been widely used for intertrochanteric fractures (2). However, it is not always possible for elderly patients with unstable fractures to have good outcomes after osteosynthesis (3,4). To address this problem, both improvement of surgical technique and advances in implant technology have been promoted (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…If starting point is placed lateral to the tip of the trochanter it may result in varus malreduction (Figure 13) [4][5][6][7].…”
Section: If Too Lateral Entry Pointmentioning
confidence: 99%
“…Some studies have reported better results with the use of SHS in intertrochanteric fracture treatment and others have stated that CMN give better results (6)(7)(8). However, the current approach to the treatment of unstable intertrochanteric fractures is the use of CMN (9)(10)(11). It has been reported that basicervical fractures could also be evaluated as unstable fractures (12).…”
Section: Introductionmentioning
confidence: 99%